2018
DOI: 10.1016/j.jiac.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of influenza virus-induced lower respiratory infection during the 2015 to 2016 season

Abstract: Allergic disease was a risk factor for developing PB due to influenza A(H1N1)pdm09 infection during the 2015-16 season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Concurring with published reports, 2,3,5,11,20 FOB appears to be safe in children, even in young or extremely premature infants. Some serious complications of the procedure, such as those of transbronchial biopsy, chronic pulmonary infiltrates, and PB, may necessitate extensive BAL 3,9,11,13 .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Concurring with published reports, 2,3,5,11,20 FOB appears to be safe in children, even in young or extremely premature infants. Some serious complications of the procedure, such as those of transbronchial biopsy, chronic pulmonary infiltrates, and PB, may necessitate extensive BAL 3,9,11,13 .…”
Section: Discussionsupporting
confidence: 68%
“…7,10 These results, consistent with the short-term fibrinolysis of PB, confirmed that early FOB and BAL were effective in the treatment of PB. 18 Concurring with published reports, 2,3,5,11,20 FOB appears to be safe in children, even in young or extremely premature infants. Some serious complications of the procedure, such as those of transbronchial biopsy, chronic pulmonary infiltrates, and PB, may necessitate extensive BAL.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…It accounted for the four fifths of influenza-related PICU admissions occurred in children with high-risk conditions. Uda et al 10 reported that among 66 patients with diagnosis of H1N1 infection 12 patients (57%) were admitted to the pediatric intensive care unit, 7 (33%) cases required mechanical ventilation. Ten patients (47%) had underlying chronic diseases such as neurological diseases, chronic lung diseases, and chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1950s, a patient expectorated spherical globules that assumed dendritic forms when placed in water [7,8]. Patients may have a history of antecedent viral infections, specifically influenza A infection [9,10].…”
Section: Clinical Featuresmentioning
confidence: 99%